Low-energy collisions between electrons and hydrogen fluoride cations. (6th November 2018) - Stroe, Marius Cristian; Fifirig, Magda
Abstract: We have studied slow electron collisions with hydrogen fluoride cations in the framework of multi-channel quantum defect theory. Assuming energy-independent interactions, the short-range reaction matrix has been evaluated in the second order of the Born expansion of the Lippmann–Schwinger equation. The isotopic effects on the cross sections and thermal rate coefficients for dissociative recombination, vibrational excitation and de-excitation have been investigated.